1977
DOI: 10.2307/3897308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gully Plugs and Contour Furrows on Erosion and Sedimentation in Cisco Basin, Utah

Abstract: Site Description B. COLTHARP The areas selected for study are located approximately 5 miles to the west and south of the town of Cisco, Grand County, Utah. This area, Highlight: The effects of contour furrows and gully plugs on known as Cisco Basin, is bounded on the north by the Book Cliffs and erosion and sedimentation within the Cisco Basin, Utah, were on the south by the Colorado River. It is typical of the upper Colorado evaluated over a 3-to byear period. Soils on the study area were River Drainage basin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…They are important for supporting the establishment of vegetation (Stokes et al, 2014), however, this can be a slow process that takes longer than the limited life expectancies of engineering measures, especially in more arid regions. For example, earthen gully plugs in Utah had life expectancies of 6 to 33 years (Gifford et al, 1977). In Ethiopia, Nyssen et al (2004) found that ~39% of check dams collapsed after just 2years.…”
Section: Long-term Management and Maintenance Of The Rehabilitation Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are important for supporting the establishment of vegetation (Stokes et al, 2014), however, this can be a slow process that takes longer than the limited life expectancies of engineering measures, especially in more arid regions. For example, earthen gully plugs in Utah had life expectancies of 6 to 33 years (Gifford et al, 1977). In Ethiopia, Nyssen et al (2004) found that ~39% of check dams collapsed after just 2years.…”
Section: Long-term Management and Maintenance Of The Rehabilitation Treatmentsmentioning
confidence: 99%
“…In Ethiopia, Nyssen et al (2004) found that ~39% of check dams collapsed after just 2years. In addition to the structural failure of check dams, soil cracking in many areas can lead to soil piping (Gifford et al, 1977), resulting in the bypassing of the dams. Also, in France, vegetated fascines showed only a limited effectiveness due to their poor maintenance (Frankl et al, 2018).…”
Section: Long-term Management and Maintenance Of The Rehabilitation Treatmentsmentioning
confidence: 99%
“…To reduce erosion in the Cisco Basin, Utah, 25,000 gully plugs and contour furrows were constructed since 1958, covering 6,000 acres. An evaluation of contour trenches and gully plugs that were constructed in four areas from 1962-1966 and evaluated from [1966][1967][1968][1969] indicated that both were effective in catching and holding sediment (Gifford et al, 1977). In areas treated with both contour trenches and gully plugs, all runoff and sediment were held on site.…”
Section: Arroyo Cutting and Gullyingmentioning
confidence: 99%
“…A description of the study area and treatments applied has been given by Gifford et al ( 1977). For this study, two 40-acre areas were selected: Area 2 in a Nuttall's saltbush (Atriplex nuttallii) community which had been treated with gully plugs and contour furrows in 1964, and Area 3 in a mat saltbush (Atriplex corrugatu) community which had been similarly treated in 1962.…”
Section: Methods and Proceduresmentioning
confidence: 99%